If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 5 = -14 Reorder the terms: 5 + -3x = -14 Solving 5 + -3x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = -14 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -14 + -5 -3x = -14 + -5 Combine like terms: -14 + -5 = -19 -3x = -19 Divide each side by '-3'. x = 6.333333333 Simplifying x = 6.333333333
| (3x^2y^3)^3/27(xy)^-9 | | 2(X)-3=4(x-1)-1-2x | | (3x^2y^3)^2/27(xy)^-9 | | f(x)=(-x^2)+(1.8x)+(2.5) | | x^2+4y^2+24y=0 | | 7-(7x+5)=13+3x | | v/2-8=22 | | 9x-25=5x-7 | | -14=-4+5v | | 5x=x-1 | | 31x=440.20 | | -6e^8x+8-3=-23 | | X-8/x^2-36 | | -16.2h=-14.67-17.1h | | 7/9x-7 | | 8(x+3)-12=2x | | 12x-3=21+3 | | 6=210-3x | | 349+x=532.93 | | 5x+5+13x-5=180 | | 2/(x-5)-1/(x-5)=11/(x-25) | | x^2-12x-9564=0 | | 10f+13=11f | | 2/(x-5)-1/(x-5)=11/(x^2-25) | | -18-12d=14-8d | | 2x^2+5(2x)= | | -2r=-1.2+9.68 | | 3x-3(4)-2x(2)= | | X+1+7x=-71 | | 4-2x(2)= | | 5a+(-6)=18 | | 19.67-9.2w-8.38=4.33+8.2w |